Centro de reacción inmediata a desastres naturales: Plan parcial renovación ciudad jardín Fusagasugá-Sumapaz-Colombia (2017)
The management and attention of disasters and disasters occupies an important space within the agenda of the national government. It is important to generate a culture in the face of disaster prevention issues, and more in a country like Colombia that due to its richness and geographical peculiarity and the human footprint in the different planned and unplanned urban processes have made management a very important aspect to work from different fronts and in an interdisciplinary way by different entities at a public and private level.